Tuberculosis among Migrant Populations in Sicily: A Field Report - Tullio Prestileo; Giuseppe Pipitone; Adriana Sanfilippo; Antonio Ficalora; Giuseppe Natoli; Salvatore Corrao; Team I. Ta. C. A. (Immigrant Take Care Advocacy) Team (Journal of Tropical Medicine)
Background. In the EU, tuberculosis (TB) mainly affects vulnerable people, including migrants. From 2014 to 2017, we have estimated the frequency of both tuberculosis and latent tuberculosis infection (LTBI) among the migrant population hosted in 41 reception centers in western Sicily (ITaCA network). Materials and Methods. All migrants were consecutively recruited for the screening of TB infection with physical examination and TST in 1,020 migrants and with IGRA in the others 2,690. The screening was carried out 4–8 weeks after landing in Sicily. For all migrants with a positive screening test, chest X-ray and smear examination were performed. LTBI was defined by positivity of TST or IGRA with negative X-ray chest, clinical, and smear examination. Active TB was defined by radiological and/or clinical and/or sputum positivity in a patient with a TST or IGRA positivity. Results. We evaluated a total of 3,710 migrants, of which 89% came from Sub-Saharan countries; 2,811 were males, 899 were females, with a median age of 22 years (IQR: 18–25). TB infection was diagnosed in 501 persons (13.5%) of which 440 (11.8%) had LTBI and 61 had active TB (1.6%): 1 had lymph node TB, 1 had intestinal TB, and 59 had pulmonary TB (38 sputum smear positive TB; no drug-resistant TB were observed). Conclusions. TB screening is critical to early diagnosis and treatment.